PENGARUH JUMLAH GIGI DI DALAM RONGA MULUT TERHADAP DAYA INGAT PADA MAHASISWA JURUSAN KESEHATAN GIGI POLTEKKES KEMENKES RI MEDAN - Ramadhan, Ety Sofia; Hamsar, Adriana (THERA-DENT (jurnal terapis gigi dan mulut), 2023)
Background: Dental and oral health is part of physical health which cannot be separated from one to another. The main problem is that many adolescents have caries and periodontal tissues which can cause the increase in tooth loss. Purpose: find out the influence of the number of teeth in oral cavity on the memory of the students of Dental Hygiene Department, Poltekkes Kemenkes RI Medan. Method: Used analytic method with cross sectional study with 60 students of Dental Hygiene Department as the samples, taken by using simple random sampling technique. The data were gathered by conducting clinical examination and questionnaires. Results: Data were analyzed by using univariate analysis and bivariate analysis with statistic chi square test. The result of the research showed that 68.3% of the respondents were in good category with the number of teeth in oral cavity, 28.3% of them were in moderate category, and 3.3% of them were in bad category. It was also found that 53.3% of the respondents had good memory, 38.3% had moderate memory, and 8.3% of them had bad memory. The result of chi square test showed Ho was rejected which indicated that there was the influence of the number of teeth in oral cavity on the memory of the students of Dental Hygiene Department, Poltekkes Kemenkes RI Medan at p-value = 0.000 (p<0.05). Conclusion : the number of teeth in oral cavity could influence the memory.